Traditional Malawian choral music : a liturgical-critical study within the Church of Central Africa Presbyterian (CCAP)-Nkhoma Synod - Katani, Archwells Moffat (Stellenbosch : Stellenbosch University, 2008)
Thesis (DTh)--Stellenbosch University, 2008.